Relationship between Brain Natriuretic Peptide and Recurrence of Atrial Fibrillation after Successful Electrical Cardioversion: an Updated Meta-Analysis - Xu,Xiangdong (2017)
Abstract Objective: To investigate the relationship between brain natriuretic peptide and recurrence of atrial fibrillation after successful electrical cardioversion. Methods: Medline and Embase databases were used to identify publications evaluating BNP/N-Terminal (NT)-proBNP levels in association with atrial fibrillation recurrence after successful electrical cardioversion. Nineteen studies that fulfilled the specified criteria of our analysis were found. Results: Baseline BNP/NT-proBNP levels of the atrial fibrillation recurrence group were significantly higher than those of the sinus rhythm maintaining group (SMD -0.70, CI [-0.82, -0.58]). Conclusion: Our analysis suggests that low BNP/NT-proBNP levels are associated with sinus rhythm maintenance, and baseline BNP/NT-proBNP concentrations may be a predictor of atrial fibrillation recurrence after successful electrical cardioversion.